2022
DOI: 10.1038/s41598-022-11022-0
|View full text |Cite
|
Sign up to set email alerts
|

Production, statistical optimization, and functional characterization of alkali stable pectate lyase of Paenibacillus lactis PKC5 for use in juice clarification

Abstract: Pectate lyase is a hydrolytic enzyme used by diverse industries to clarify food. The enzyme occupies a 25% share of the total enzyme used in food industries, and their demand is increasing gradually. Most of the enzymes in the market belong to the fungal origin and take more time to produce with high viscosity in the fermentation medium, limiting its use. The bacteria belonging to the genus Bacillus have vast potential to produce diverse metabolites of industrial importance. The present experiment aimed to iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…This indicates that metal ions such as Mg 2+ play an important role in maintaining the active conformation of pectinase to stimulate enzyme activity (Oumer and Abate, 2017). The results are the same as the increase in pectinase activity by Mg 2+ ions, namely Bacillus subtilis isolated from kimchi (traditional Korean food) (Rahman et al, 2020), Bacillus subtilis strain Btk 27 (Oumer and Abate, 2017), and Paenibacillus lactis isolated from the coast (Sheladiya et al, 2022). In contrast, different results were reported that the pectinase activity of Bacillus subtilis isolated from the sea was inhibited by 10 mM Mg 2+ ions, and the pectinase was increased when Fe 2+ ions were added (Joshi et al 2015).…”
Section: Metals Ions Effect On Pectinase Activitymentioning
confidence: 81%
See 1 more Smart Citation
“…This indicates that metal ions such as Mg 2+ play an important role in maintaining the active conformation of pectinase to stimulate enzyme activity (Oumer and Abate, 2017). The results are the same as the increase in pectinase activity by Mg 2+ ions, namely Bacillus subtilis isolated from kimchi (traditional Korean food) (Rahman et al, 2020), Bacillus subtilis strain Btk 27 (Oumer and Abate, 2017), and Paenibacillus lactis isolated from the coast (Sheladiya et al, 2022). In contrast, different results were reported that the pectinase activity of Bacillus subtilis isolated from the sea was inhibited by 10 mM Mg 2+ ions, and the pectinase was increased when Fe 2+ ions were added (Joshi et al 2015).…”
Section: Metals Ions Effect On Pectinase Activitymentioning
confidence: 81%
“…These results indicate that enzymes from different sources require various metal ions at certain concentrations to carry out the activity. In addition, the evolution of enzymes also determines the need for metal ions at the active site because microorganisms evolve according to the surrounding environment to survive and grow well so they tend to modify their metabolic pathways or enzymes (Sheladiya et al, 2022).…”
Section: Metals Ions Effect On Pectinase Activitymentioning
confidence: 99%
“…The DNA of bacteria was isolated by the LSP buffer method (Sheladiya et al, 2022 ). The 16S rRNA gene-specific primer; 27F 5‘AGAGTTTGATCCTGGCTCAG-3' and 1492R 5‘GGTTACCTTGTTACGACTT 3' were used to amplify the target sequence of 1,500 bp.…”
Section: Methodsmentioning
confidence: 99%
“…Post-incubation, CFCS aliquots were drawn at 0 and 48 h to assess pectinase activity, amount of reducing sugar, [26] and the change in pH.…”
Section: Factors Affecting Pectinase Production By B Vallismortis Mh 10mentioning
confidence: 99%